The Centrality of Language in Human Cognition. Issue 3 (11th December 2015) - Lupyan, Gary
Abstract : The emergence of language—a productive and combinatorial system of communication—has been hailed as one of the major transitions in evolution. By enabling symbolic culture, language allows humans to draw on and expand on the knowledge of their ancestors and peers. A common assumption among linguists and psychologists is that although language is critical to our ability to share our thoughts, it plays a minor, if any, role in generating, controlling, and structuring them. I examine some assumptions that led to this view of language and discuss an alternative according to which normal human cognition is language‐augmented cognition. I focus on one of the fundamental design features of language—the use of words as symbolic cues—and argue that language acts as a high‐level control system for the mind, allowing individuals to sculpt mental representations of others as well as their own.